Composition of termites in three different soil types across oil palm agroecosystem regions in Riau (Indonesia) and Johor (Peninsular Malaysia) - Saputra A.; Muhammad Nasir D.; Jalaludin N.-A.; Halim M.; Bakri A.; Mohammad Esa M.F.; Riza Hazmi I.; Faszly Rahim (Lembaga Minyak Sawit Malaysia, 2024)
Termites are perceived as decomposers and as pests in an ecosystem. A study on the species composition of termites in different soil types (i.e. clay, sand and peat) in oil palm plantations was conducted between 6 April 2015 and 10 December 2015 in nine selected localities in Johor (Malaysia) and Riau (Indonesia). Sampling of termites was conducted using belt transects of 100 m in length and 4 m in width in the oil palm plantation. A total of three replicates for each soil types were done from the nine transects for each location. A total of 41 species from five subfamilies (i.e. Coptotermitinae, Rhinotermitinae, Termitinae, Macrotermitinae and Nasutitemitinae) and two families (i.e. Rhinotermitidae and Termitidae) of termite species were successfully sampled and recorded. Sand soil (81 colonies: 12 species; four subfamilies; two families) recorded the highest colonies, followed by peat soil (62 colonies: 12 species; five subfamilies; two families), and clay soil (47 colonies consisting; nine species, four subfamilies and two families). There was a significant difference (?2 = 618 886, df = 328, p<0.005) between soil types and termite species composition that were found in the oil palm plantation. This study identified that the diversity and abundance of termites differed between soil types in different oil palm plantations.